Glancing angle deposited Ni nanopillars coated with conformal, thin layers of Pt by a novel electrodeposition: Application to the oxygen reduction reaction. (1st January 2015) - Xu, Shuai; Wang, Chao; Francis, Sonja A.; Tucker, Ryan T.; Sorge, Jason B.; Moghaddam, Reza B.; Brett, Michael J.; Bergens, Steven H.
Highlights: Uniform deposition of Pt under a novel rotating disc condition on GLAD (glancing angle deposited) Ni with use of the counter electrode as Pt source. Strong attachment of the deposited Pt without using binder agents. Superior activity of NiGLAD Pt/GC to Pt/GC towards oxygen reduction in base. Significant durability of NiGLAD Pt/GC in long term oxygen reduction. Abstract: Glancing Angle Deposition (GLAD) was used to prepare 500 nm long Ni nanopillars directly on glassy carbon disc electrodes (NiGLAD /GC). NiGLAD Pt/GC core-layer nanopillars were prepared by depositing Pt on the NiGLAD substrate via a novel rotating disc electrode galvanostatic deposition, where a stationary blackened Pt counter electrode served as the Pt source. Scanning electron microscopy, cyclic voltammetry, and inductively-coupled mass spectrometry were employed to characterize the deposits. Results indicated that the Pt was deposited in a conformal manner on the NiGLAD giving a loading of 11.6 μg. The NiGLAD Pt/GC electrode was ca. three fold more active than a Pt/GC (made with the same deposition in the absence of Ni) towards the oxygen reduction reaction (ORR) in 1.0 M KOH. As well, long term potentiostatic ORR studies showed the NiGLAD Pt/GC deposit was more durable than the Pt/GC, with the former completely retaining its initial performance after 5000 s polarization at 0.85 V vs. RHE, while Pt/GC lost 38% of its activity. Subsequent control experiments in the absence of O2 showed that such decay was not due to loss of Pt over the prolonged ORR.